Diseño y Construcción de un Sistema Seguidor de Sol con Modelo Astronómico (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2011)
This paper presents the most important aspects about the design and construction of a two axis sun tracker with astronomic model with capacity for positioning a 80 W photovoltaic panel.